Microstructural effects of high-energy grinding on poorly soluble drugs: the case study of efavirenz. (21st February 2017) - Cappelletto, Elisa; Rebuffi, Luca; Flor, Alberto; Scardi, Paolo
Abstract : In this work, a poorly water-soluble drug (efavirenz) was mechanically activated by ball-milling. The effect of the mechanical activation on the dissolution behavior was investigated considering changes in the particle size and morphology. The powder diffraction was used to follow the comminution process, verifying phase compositions, and crystalline domain size. The interplay between domain and grain size was studied in relation to the solubility rate, through specific dissolution tests. Finally, the morphological characterization has allowed to complete the physical–chemical characterization of the milled powders. This study demonstrated that the mechanical activation of the drug leads the particle size reduction and, with a long milling time, morphological changes. The grain size reduction is not always sufficient to increase the solubility: morphology and agglomeration grade play an important role in the dissolution process.